VOICE RECOGNIZATION FOR MOUSE CONTROL USING HCI (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
One  of  the  most  important  research  areas  in  the  field  of  Human -Computer-Interaction (HCI) is gesture  recognition as it provides a natural and intuitive  way  to  communicate  between  people  and  machines.  Voice-based HCI applications range from computer applications to virtual/augmented reality and is recently being explored in other fields. This work proposes the implementation of absolute virtual mouse based on the interpretation of voice reorganization control. The procedure is to control the mouse pointer as for the mouse movement to up/down/left/right, open the file, dragging the file. This  virtual  device  is designed  specifically  as  an  alternative non-contact  pointer  for  people  with mobility impairments in the upper extremities. The implementation of the virtual mouse by voice control is to make HCI simplification for disabled persons especially for the person who are not having the hands and arms, and Alternative mouse cursor positioning system for laptops.